Extended Abstracts of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411763.3441342
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing Human-Centered Perspectives in Explainable AI

Abstract: The realm of Artifcial Intelligence (AI)'s impact on our lives is far reaching -with AI systems proliferating high-stakes domains such as healthcare, fnance, mobility, law, etc., these systems must be able to explain their decision to diverse end-users comprehensibly. Yet the discourse of Explainable AI (XAI) has been predominantly focused on algorithm-centered approaches, sufering from gaps in meeting user needs and exacerbating issues of algorithmic opacity. To address these issues, researchers have called f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 26 publications
0
40
0
2
Order By: Relevance
“…A full review of XAI techniques is beyond the scope of this paper and can be found in many recent survey papers [1,29,55,56]. Our work is most closely informed by, and intends to bridge, the emerging topic of explainability for generative models, and the inter-disciplinary field of Human-Centered Explainable AI (HCXAI) [21,22,52].…”
Section: Explainable Aimentioning
confidence: 99%
See 2 more Smart Citations
“…A full review of XAI techniques is beyond the scope of this paper and can be found in many recent survey papers [1,29,55,56]. Our work is most closely informed by, and intends to bridge, the emerging topic of explainability for generative models, and the inter-disciplinary field of Human-Centered Explainable AI (HCXAI) [21,22,52].…”
Section: Explainable Aimentioning
confidence: 99%
“…The term Human-centered AI has emerged in many academic works and public discussions [22,25,45,65,85,89]. While definitions vary, human-centered approaches to AI aim to develop AI systems that serve the needs, improve the conditions, and align with the values of human stakeholders.…”
Section: Human-centered Approaches To Aimentioning
confidence: 99%
See 1 more Smart Citation
“…With an increasing number of XAI methods, the demand grows for suitable XAI evaluation metrics [1,21,29,86,146]. This need is not only recognized by the AI community; also the Human Computing Interaction (HCI) community is concerned with developing transferable evaluation methods for XAI [65]. In addition, a research agenda for Hybrid Intelligence [6] has explicitly formulated a research question asking how the quality and strength of explanations can be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying the experience of users cooperating with intelligent systems is a challenging task and many different instruments emerge to support XAI research [41]. Empirically validated tools are crucial in order to 1) research explainable artificial intelligence (XAI) as well as 2) improve transparency for users of, e.g., machine learning models [10]. While tackling the disadvantages of opaque systems, many approaches aim to improve conditions for joint human-AI activity [23] by providing, e.g., visual explanations of the system's information processing [5].…”
Section: Introductionmentioning
confidence: 99%